1983
DOI: 10.1111/j.1464-410x.1983.tb03297.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the Urinary Bladder in Zambia. A Quantitative Estimation of Schistosoma haematobiumInfection

Abstract: The incidence and intensity of schistosomal infection in 50 African malignant bladders determined by quantitative analysis have been compared with a matched control group of nonmalignant cadaver bladders, and the incidence of radiological calcification in the former has been compared with that of 50 adult urinary bilharziasis patients without associated malignancy. Compared with 45% in the non-malignant group, schistosomal infection was present in an overwhelming 94% of the malignant cases. Radiological calcif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] The epidemiologic association is based both on case-control studies, 1,2,5,10 and on the close correlation of bladder cancer incidence with prevalence of S. haematobium infection within different geographic areas. [5][6][7][8]11 A parasite-tumor linkage is further suggested by the predominance of squamous cell (as opposed to transitional cell) morphology of bladder carcinomas seen in S. haematobium-endemic areas, and by the frequent association of tumors with parasite eggs and egg-induced granulomatous pathology in involved bladder tissues. 12 In non-endemic countries, urine sediment cytology has proven to be a sensitive and specific technique for detecting more aggressive carcinomas of the urinary tract in patients with symptomatic urinary tract disease.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The epidemiologic association is based both on case-control studies, 1,2,5,10 and on the close correlation of bladder cancer incidence with prevalence of S. haematobium infection within different geographic areas. [5][6][7][8]11 A parasite-tumor linkage is further suggested by the predominance of squamous cell (as opposed to transitional cell) morphology of bladder carcinomas seen in S. haematobium-endemic areas, and by the frequent association of tumors with parasite eggs and egg-induced granulomatous pathology in involved bladder tissues. 12 In non-endemic countries, urine sediment cytology has proven to be a sensitive and specific technique for detecting more aggressive carcinomas of the urinary tract in patients with symptomatic urinary tract disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the Nile delta, mixed infection with S. haematobium and S. mansoni is endemic, while S. haematobium is more prevalent in Upper Egypt because of the specific locations of the intermediate snail hosts. In other countries including Iraq, Malawi, Zambia and Kuwait where either mixed or S. haematobium infestation is endemic, there is also a high incidence of bladder cancer cases associated with schistosomiasis and has also been reported to be the leading malignant disease (Lucas, 1982; Elem and Purohit, 1983; Al‐Shukri et al , 1987; Al‐Saleem et al , 1990).…”
Section: Discussionmentioning
confidence: 99%
“…For example, squamous cell carcinoma of the urinary bladder has been associated with Schistosoma haematobium infection in studies in many areas of Africa [55-63]. In addition, studies from Africa have shown that the estimated incidence of urinary bladder cancer is higher in areas with a high prevalence of infection with S. haematobium , compared to areas with a low prevalence.…”
Section: Pathology and Morbiditymentioning
confidence: 99%